Processing metabolomics and proteomics data with open software : a practical guide - Winkler, Robert (New developments in mass spectrometry ;, 2020)
Metabolomics and proteomics allow deep insights into the chemistry and physiological processes of biological systems. This book will enable researchers, practitioners and students from different backgrounds to analyze metabolomics and proteomics mass spectrometry data.